ORBITAL ANGULAR MOMENTUM-BASED SLOT ARRAY ANTENNA FOR MODERN APPLICATIONS - Mousa Majeed, Arkan; Elwi, Taha A.; Abdul Hassain, Zaid A.; Kumar, Jayendra; E. Saleem, Ahmed (Journal of Engineering and Sustainable Development, 2024)
Millimeter waves are the most promising waves for different modern wireless communication networks. This is due to their ability to carry big data with enhanced channel capacity. However, mm-waves suffer from low propagation due to the effects of high attenuation factors with high frequencies. Therefore, in this work, a three-dimensional structural antenna design with a slot array is proposed to achieve high gain through a two-port feeding operation for orbital angular momentum applications of modern communication systems. Also, the improved bandwidth of the proposed antenna makes it an excellent candidate for fifth-generation (5G) communications systems. The antenna depends on two concentric structures with conductive circular cross-sectional area. The first structure is shaped as a three-dimensional cone with a cylindrical waveguide. The second structure is shaped as a circular disc with a circular aperture. The two parts of the proposed antenna are concentered to be fed with two discrete ports from the side with a 900phase difference. It is determined that the proposed antenna offers an exceptional gain to vary from 10dBi to 20dBi within the frequency band from 3GHz to 30GHz. It is realized that such enhancement after introducing a conductive circular reflector underneath the conductive cone. The antenna shows a matching impedance below -10dB over the entire frequency band of interest. The antenna radiation proprietors at 25GHz and 26GHz at the E-plane and H-plane are characterized. Finally, the antenna performance is validated using two software packages based on CST studio and HFSS algorithms.